(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
The Covid-19 pandemic has led to eating habits and lifestyle changes. This change is due to online learning and increased awareness of healthy living. This research aims to analyze the correlation between nutritional knowledge, changes in eating habits, and lifestyle with the nutritional status of undergraduate students during the pandemic. The design of this research was a cross-sectional study conducted from April until July 2021. Data collection is done through an online survey using validated questionnaires, interviews by WhatsApp call, and self-reported anthropometric data. The results showed that most of the subjects had normal nutritional status (54,7%). The level of subject nutritional knowledge is good and fair with an average score of 82.5. The highest percentage of changes in eating habits was the increase in fruit and vegetable consumption (66.7%). The highest percentage of lifestyle changes was the increase in wearing masks habit every time the subject go outside (94.7%). The results of the Spearman correlation test showed that was no significant relationship (p-value>0.05) between the score of nutritional knowledge, eating habits, and lifestyle changes with the Body Mass Index (BMI). However, research results show that during the pandemic there has been a change in eating habits and lifestyle in a healthier direction despite a decrease in physical activity.